TEACHERS’ PERCEPTION TOWARDS THE USE OF VISUAL LEARNING AIDS IN EFL CLASSROOM - Retno Wiyati; Feni Marlina (JELA (Journal of English Language Teaching, Literature and Applied Linguistics), 2021)
This study was aimed at describing the kind of visual learning aids used by teachers and teachers’ perception towards the use of visual learning aids in EFL classroom. This study was a descriptive study. There were questionnaire and interview as data collecting technique in this study. The participants were three English teachers. The findings showed that teachers used several kinds of visual learning aids in their teaching and learning process, there were blackboard, textbook, real object, picture file, chart, pocket chart, flash card, word card, number card, projector, and slideshow. Furthermore, teachers gave positive feedback 53.33% towards the use of visual learning aids in EFL classroom. The use of visual learning aids assisted teachers in conducting teaching and learning process and also assisted teachers in managing teachers’ time both in preparing the lesson and during the lesson. To conclude, teachers used several kinds of visual learning aids in assisting them to conduct a better learning situation and provide well management time in preparing the lesson and during the lesson.